Challenges and Opportunities for Bio-oil Refining: A Review - Pinheiro Pires, Anamaria Paiva; Arauzo, Jesus; Fonts, Isabel; Domine, Marcelo E; Fernández Arroyo, Alberto; Garcia-Perez, Marta Estrella; Montoya, Jorge; Chejne, Farid; Pfromm, Peter; Garcia-Perez, Manuel (Energy & fuels, 2019)
Bio-oil derived from fast pyrolysis of lignocellulosic materials is among the most complex and inexpensive raw oils that can be produced today. Although commercial or demonstration scale fast pyrolysis units can readily produce this oil, the pyrolysis industry has not grown to significant commercial impact due to the lack of bio-oil market pull. This paper is a review of the challenges and opportunities for bio-oil upgrading and refining. Pyrolysis oil consists of six major fractions (water 15–30 wt %, light oxygenates 8–26 wt %, monophenols 2–7 wt %, water insoluble oligomers derived from lignin 15–25 wt %, and water-soluble molecules 10–30 wt %). The composition of water-soluble oligomers is relatively poorly studied. In the 1880s, bio-oil refining (formally known as wood distillation) targeted the separation and commercialization of C1–C4 light oxygenated compounds to produce methanol, acetic acid, and acetone with the commercialization of the lignin derived water insoluble fraction for preserving wooden sailing vessels against rot. More recently, the company Ensyn extracted and commercialized condensed natural smoke as a food additive. Most research efforts in the last 20 years have focused on the two-step hydrotreatment concept for the production of transportation fuels. In spite of major progress, this concept remains at the demonstration scale. In this review, the opportunities and progress to separate bio-oil fractions and chemicals, mainly acetic acid (HAc), hydroxyacetaldehyde (HHA), acetol, and levoglucosan, and convert them into value added coproducts are thoroughly discussed. In spite of the large number of separation schemes and products tested, very few of them have been tested as part of fully integrated bio-oil refinery concepts. The synthesis and techno-economic and environmental evaluation of novel integrated bio-oil refinery concepts is likely to become a subject of intense research activity in the coming years.